On the effects of hydrogen addition in premixed formaldehyde flames. (9th February 2017) - Luo, Minye; Liu, Dong
Abstract: The influences of hydrogen addition on laminar premixed fuel-rich formaldehyde flames at the atmospheric pressure are studied by the detailed kinetic analysis. The chemical effects of hydrogen addition on flame structures, mole fractions of major species and free radicals are distinguished clearly from the dilution and thermal effects. The results show that the H2 chemical effects can promote the oxidation of formaldehyde and make the mole fraction profile of formaldehyde move toward the upstream side. The increase of H radical concentration is mainly due to the chemical effects of hydrogen addition. The reaction OH + H2 = H + H2 O plays a major role in the productions of H and OH radicals. The productions of O, HCO and HO2 radicals are enhanced by the H2 chemical effects. However, the hydrogen dilution and thermal effects on decreasing these radicals' concentrations are more dominant. The mole fractions of CO and CO2 decrease with H2 addition. The H2 chemical effects facilitate the formation of CO, but suppress the production of CO2 . Highlights: H2 chemical effects on CH2 O/H2 flames are isolated from thermal/dilution effects. H concentrations increase due to significant H2 chemical effects. H2 dilution and thermal effects reduce O, OH, HCO and HO2 concentrations. CO2 formation is suppressed predominantly by chemical effects of H2 addition.